2019
DOI: 10.3390/nano9020168
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus Nano-Polarizer with High Extinction Ratio in Visible and Near-Infrared Regime

Abstract: We study computationally the design of a high extinction ratio nano polarizer based on black phosphorus (BP). A scattering-matrix calculation method is applied to compute the overall polarization extinction ratio along two orthogonal directions. The results reveal that, with a resonance cavity of SiO2, both BP/ SiO 2 /Si and h-BN/BP/ SiO 2 /Si configurations can build a linear polarizer with extinction ratio higher than 16 dB at a polarized wavelength in the range of 400 nm–900 nm. The polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…[235] The absorption wavelength is also highly tunable by the thickness of SiO 2 and BP. [233,236] A theoretical calculation reveals that ultra-broadband anisotropic absorption can be achieved in patterned (BP/dielectric) n multilayers. [237] These structures hold promise in applications in optical absorbers, reflective polarizers, and beam splitters with high polarization and wide bandwidth.…”
Section: Optical Componentsmentioning
confidence: 99%
“…[235] The absorption wavelength is also highly tunable by the thickness of SiO 2 and BP. [233,236] A theoretical calculation reveals that ultra-broadband anisotropic absorption can be achieved in patterned (BP/dielectric) n multilayers. [237] These structures hold promise in applications in optical absorbers, reflective polarizers, and beam splitters with high polarization and wide bandwidth.…”
Section: Optical Componentsmentioning
confidence: 99%
“…This phenomena can be understood by treating the oxidized layer as a transparent layer, like SiO 2 , considering its refractive index around 1.57. [45,46] We first pay our attention to flake No. 2 in Figure 4a, which is a simple case that BP's thickness is within the first coherent interference range.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the in-plane direction and out-of-plane direction absorption capabilities of 2D materials are different due to their natural optical anisotropy. , Based on the optical anisotropy of 2D materials, a variety of polarizers have been developed recently. For example, in 2017, Lin et al experimentally demonstrated a broadband and high extinction-ratio graphene-based waveguide polarizer Figure a,b shows a schematic and a cross-sectional view SEM image, respectively, of the graphene-based waveguide polarizer.…”
Section: Metaphotonic Devices Based On 2d Materialsmentioning
confidence: 99%